Radio Frequency Identification (RFID) inventory tag / Iqbal Nahar and Muhammad Redza Rosman - Nahar, Iqbal; Rosman, Muhammad Redza (2023)
This research delves into the transformative potential of RFID inventory tags, aiming to revolutionise stock management systems and address persistent challenges in traditional inventory methods. Despite the existence of RFID technology for over six decades, its continued implementation remains pivotal in contemporary markets, offering a powerful solution to enhance efficiency and accuracy in stock management. Conventional inventory management techniques often struggle with slow tracking processes of incoming and outgoing stock, leading to detrimental consequences like missed sales opportunities, inaccurate inventory planning, and delays in restocking. The lack of real-time visibility in traditional systems hampers businesses’ ability to promptly monitor inventory movement and respond rapidly to fluctuations in demand or supply. To overcome these limitations, the research passionately advocates for the seamless integration of RFID electronic tags on the production line and harnessing the automation and monitoring capabilities bestowed by RFID technology. The primary objectives encompass streamlining stock checking and restocking procedures, mitigating errors in stock checking, and establishing real-time tracking mechanisms for remaining and incoming stocks.